Meteorological Data at Japanese Ny-Ålesund Observatory, Svalbard in 1999 and 2000 - モリモト, シンジ; アオキ, シュウジ; ナカニシ, ユウジ; ワダ, マコト; ヤマノウチ, タカシ; Morimoto, Shinji; Aoki, Shuhji; Nakanishi, Yuji; Wada, Makoto; Yamanouchi, Takashi (National Institute of Polar Research, 2002)
P(論文) Dataset : Meteorological Data at Japanese Ny-Alesund Observatory, Svalbard in 1999 and 2000. | https://ads.nipr.ac.jp/dataset/A20131010-005 departmental bulletin paper